Adenoid cystic carcinoma evaluation and management: progress with optimism!. Issue 2 (April 2017) - Bradley, Patrick J.
Abstract : Purpose of review: Adenoid cystic carcinoma (ACC) when diagnosed presents several diagnostic and treatment challenges. The standard treatment of surgery and postoperative radiotherapy has remained the standard of care for the past 3 decades. The purpose of this review is to update what's been reported and what's new since the last review in 2004. Recent findings: As accurate a histological diagnosis and staging of disease should be achieved prior to commencing any treatment. Patients' prognosis, in the long term, is determined by the finding of any solid tumour component in the examined excised specimen. The continued treatment of patients with ACC by surgery and postoperative radiotherapy has not changed in the long-term tumour-free outcome of patients. The majority of patients die because of loco-regional failure and/or distant metastases. Optimism is being generated by the findings at the molecular and genetic level of ACC giving hope that nonsurgical treatment can be complemented by novel treatments that will improve patients' disease cure and improved long-term survival. Summary: The histological grading determined by optical methods has not advanced our selection of treatment and new recent research findings on molecular and genetic factors give new hopes to changing the ACC classification, determining differing treatments and thus influencing an improved and prolonged tumour-free survival for more patients.